Mapping the Gene Expression Spectrum of Mediator Subunits in Response to Viroid Infection in Plants - Nath, Vishnu Sukumari; Shrestha, Ankita; Awasthi, Praveen; Mishra, Ajay Kumar; Kocábek, Tomáš; Matoušek, Jaroslav; Sečnik, Andrej; Jakše, Jernej; Radišek, Sebastjan; Hallan, Vipin (International journal of molecular sciences, 2020)
The mediator (MED) represents a large, conserved, multi-subunit protein complex that regulates gene expression through interactions with RNA polymerase II and enhancer-bound transcription factors. Expanding research accomplishments suggest the predominant role of plant MED subunits in the regulation of various physiological and developmental processes, including the biotic stress response against bacterial and fungal pathogens. However, the involvement of MED subunits in virus/viroid pathogenesis remains elusive. In this study, we investigated for the first time the gene expression modulation of selected MED subunits in response to five viroid species (Apple fruit crinkle viroid (AFCVd), Citrus bark cracking viroid (CBCVd), Hop latent viroid (HLVd), Hop stunt viroid (HSVd), and Potato spindle tuber viroid (PSTVd)) in two model plant species (Nicotiana tabacum and N. benthamiana) and a commercially important hop (Humulus lupulus) cultivar. Our results showed a differential expression pattern of MED subunits in response to a viroid infection. The individual plant MED subunits displayed a differential and tailored expression pattern in response to different viroid species, suggesting that the MED expression is viroid- and plant species-dependent. The explicit evidence obtained from our results warrants further investigation into the association of the MED subunit with symptom development. Together, we provide a comprehensive portrait of MED subunit expression in response to viroid infection and a plausible involvement of MED subunits in fine-tuning transcriptional reprogramming in response to viroid infection, suggesting them as a potential candidate for rewiring the defense response network in plants against pathogens.
Keywords: Gene Expression Regulation, Plant; rostlinné viry; Gene Expression Profiling; stanovení celkové genové exprese; mediátorový komplex; rostlinné proteiny; Plant Leaves; viroidy; Species Specificity; regulace genové exprese u rostlin; druhová specificita; Plant Proteins; tabák; Plant Viruses; Viroids; Mediator Complex; Nicotiana; listy rostlin; Humulus